Enhanced fluorescence of tetrasulfonated zinc phthalocyanine by graphene quantum dots and its application in molecular sensing/imaging. (10th October 2016) - Wang, Jian; Zhang, Yanjun; Ye, Jiqing; Jiang, Zhou
Abstract: When excited at 435 nm, tetra‐sulfonate zinc phthalocyanine (ZnPcS4 ) emitted dual fluorescence at 495 and 702 nm. The abnormal fluorescence at 495 nm was experimentally studied and analyzed in detail for the first time. The abnormal fluorescence at 495 nm was deduced to originate from triplet–triplet (T–T) energy transfer of excited phthalocyanine ( 3 *ZnPcS4 ). Furthermore, graphene quantum dots (GQDs) enhanced the 495 nm fluorescence quantum yield ( Q ) of ZnPcS4 . The fluorescence properties of ZnPcS4 –GQDs conjugate were retained in a cellular environment. Based on the fluorescence of ZnPcS4 –GQDs conjugate, we designed and prepared an Apt29/thrombin/Apt15 sandwich thrombin sensor with high specificity and affinity. This cost‐saving, simple operational sensing strategy can be extended to use in sensing/imaging of other biomolecules.